Pengaruh Pemberian Compression Stocking dan Head Up 30 Derajat Terhadap Pencegahan Hipotensi Ortostatik pada Pasien Post Operasi di Rumah Sakit BIMC Nusa Dua - Luh Ari Suantari; Arik Juliana Putra Kmg; Ni Putu Nita Ayu Sandra (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Orthostatic hypotension is a common disorder characterized by a decrease in blood pressure when standing. with significant prevalence, non-pharmacological therapy such as the use of compression stockings is considered effective. The aim of the research is to determine the effect of giving compression stockings and a 30 degree head up on the prevention of orthostatic hypotension in post-operative patients at BIMC NUSA DUA Hospital. This research method uses a quasi-experimental design to evaluate the effect of compression stockings and a 30 degree head position on the prevention of orthostatic hypotension in post-operative patients at BIMC Nusa Dua Hospital. The study population consisted of all post-operative patients, an average of 60 people per month, and samples were obtained using non-probability sampling techniques, with a total sample size of 38 people. Blood pressure data was processed and analyzed using univariate and bivariate analysis, including the Wilcoxon test to compare differences in blood pressure scores before and after treatment. The results of research on post-operative patients at BIMC Nusa Dua Hospital showed that the majority were aged 36 - 45 years as many as 11 people (28.9%), while the majority of female patients were 25 people (65.8%), and 24 people (63.2%). ) has no history of disease. The provision of compression stockings resulted in around 63.2% of patients being free from orthostatic hypotension, while 26.3% experienced mild hypotension. The combination of compression stockings and an upright head position of 30 degrees showed that around 78.9% of patients experienced orthostatic hypotension. did not experience orthostatic hypotension, with 21.1% experiencing mild hypotension. Conclusion: Giving compression stockings resulted in 63.2% of patients being free from orthostatic hypotension, while the combination with a head position above 30 degrees achieved 78.9%. Statistical analysis confirmed the effectiveness of combination treatment in preventing orthostatic hypotension. Keywords: Compression Stockings, 30 Degree Head-Up Position, Orthostatic Hypotension Postoperative Patients  ABSTRAK Hipotensi ortostatik merupakan kelainan umum yang ditandai dengan penurunan tekanan darah saat berdiri. dengan prevalensi yang signifikan, terapi nonfarmakologis seperti penggunaan stoking kompresi dinilai efektif. tujuan penelitian adalah untuk mengetahui pengaruh pemberian compression stocking dan head up 30 derajat terhadap pencegahan hipotensi ortostatik pada pasien post operasi DI Rumah Sakit BIMC NUSA DUA Metode penelitian ini menggunakan desain quasi eksperimental untuk mengevaluasi pengaruh stocking kompresi dan posisi kepala 30 derajat terhadap pencegahan hipotensi ortostatik pada pasien pasca operasi di RS BIMC Nusa Dua. Populasi penelitian terdiri dari seluruh pasien pasca operasi, rata-rata 60 orang per bulan, dan sampel diperoleh dengan menggunakan teknik non-probability sampling, dengan jumlah sampel total 38 orang. Data tekanan darah diolah dan dianalisis menggunakan analisis univariat dan bivariat, termasuk uji Wilcoxon untuk membandingkan perbedaan skor tekanan darah sebelum dan sesudah perlakuan. Hasil penelitian terhadap pasien pasca operasi di RS BIMC Nusa Dua menunjukkan mayoritas berusia 36 – 45 tahun sebanyak 11 orang (28,9%), sedangkan pasien perempuan terbanyak sebanyak 25 orang (65,8%), dan 24 orang (63,2%) tidak mempunyai riwayat penyakit. Pemberian stoking kompresi menghasilkan sekitar 63,2% pasien terbebas dari hipotensi ortostatik, sedangkan 26,3% mengalami hipotensi ringan. Penggunaan kombinasi stoking kompresi dan posisi kepala tegak 30 derajat menunjukkan sekitar 78,9% pasien mengalami hipotensi ortostatik. tidak mengalami hipotensi ortostatik, dengan 21,1% mengalami hipotensi ringan. Kesimpulan Pemberian stoking kompresi menghasilkan 63,2% pasien terbebas dari hipotensi ortostatik, sedangkan kombinasi dengan posisi kepala di atas 30 derajat mencapai 78,9%. Analisis statistik mengkonfirmasi efektivitas pengobatan kombinasi dalam mencegah hipotensi ortostatik. Kata Kunci: Stocking Kompresi, Posisi Head-Up 30 Derajat, Hipotensi Ortostatik, Pasien Pasca Operasi